2002
DOI: 10.2298/vsp0202203m
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing fasciitis caused by group A streptococcus

Abstract: The first case of the confirmed necrotizing fasciitis caused by Group A Streptococcus in Yugoslavia was presented. Male patient, aged 28, in good health, suddenly developed symptoms and signs of severe infective syndrome and intensive pain in the axillary region. Parenteral antibiotic, substitutional and supportive therapy was conducted along with the radical surgical excision of the necrotizing tissue. The patient did not develop streptococcal toxic shock syndrome thanks to the early established diagnosis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…There was a significant correlation between STSS and prognosis. In patients with STSS, mortality is about 80%–100%, while in those without STSS, mortality is about 30% 21 . The time of diagnosis of NF is also important to prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a significant correlation between STSS and prognosis. In patients with STSS, mortality is about 80%–100%, while in those without STSS, mortality is about 30% 21 . The time of diagnosis of NF is also important to prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with STSS, mortality is about 80%-100%, while in those without STSS, mortality is about 30%. 21 The time of diagnosis of NF is also important to prognosis. Multivariate logistic regression analysis showed that surgical debridement time delay of more than 24 h from admission was the only independent risk factor for prognosis after adjusting for age, sex, diabetes, and hypotension on admission.…”
Section: Discussionmentioning
confidence: 99%
“…GAS infection-related in-hospital case fatality rate is reported to be about 11% [ 1 ]. The incidence of the GAS infection has been reported to increase during the last 10–20 years due to the increasing colonization of the GAS in general population [ 2 ]. Hemolytic streptococcus gangrene is a fatal disease that causes systemic illness and multisystem failures, such as bacteremia, renal impairment, hepatitis, acute thrombocytopenia and respiratory failure.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperbaric oxygen as an adjunct treatment 3,15,18 . has been discussed upon but it has been decided not to be used because of clinical and radiological signs of good response on 9 previous therapeutic modalities and in order to accelerate closure of stump wound by administering negative pressure therapy.…”
mentioning
confidence: 99%